Influence of sterilisation methods on collagen-based devices stability and properties - Delgado, Luis M; Pandit, Abhay; Zeugolis, Dimitrios I (Expert review of medical devices, 2014)
Sterilisation is essential for any implantable medical device in order to prevent infection in patients. The selection of the most appropriate sterilisation method depends on the nature and the physical state of the material to be sterilised; the influence of the sterilisation method on the properties of the device; and the type of the potential contaminant. In this context, herein we review the influence of ethylene oxide, γ-irradiation, e-beam irradiation, gas plasma, peracetic acid and ethanol on structural, biomechanical, biochemical and biological properties of collagen-based devices. Data to-date demonstrate that chemical approaches are associated with cytotoxicity, whilst physical methods are associated with degradation, subject to the device physical characteristics. Thus, the sterilisation method of choice is device dependent.